Serum uric acid increases in patients with systemic autoimmune rheumatic diseases after 3 months of treatment with TNF inhibitors - Hasikova, Lenka; Pavlikova, Marketa; Hulejova, Hana; Kozlik, Petr; Kalikova, Kveta; Mahajan, Aparna; Herrmann, Martin; Stiburkova, Blanka; Zavada, Jakub (Rheumatology International, 2019)
In patients with gout, the serum uric acid (SUA) is usually lower during acute gouty attacks than during intercritical periods. It has been suggested that systemic inflammatory response can cause this phenomenon. The objective is to determine whether therapy with TNF inhibitors (TNFis) affects SUA levels in patients with systemic autoimmune rheumatic diseases (SARDs) and whether SUA changes correlate with pro-inflammatory cytokines or with the oxidative stress marker allantoin. In this study, SUA, CRP, creatinine, MCP-1, IFN-α2, IFN-γ, Il-1β, IL-6, IL-8, IL-10, IL-12, IL-17a, IL-18, IL-23, IL-33, TNF-α, and allantoin levels were measured prior to and after 3 months of TNFis treatment in patients with SARDs. The values obtained in the biochemical assays were then tested for associations with the patients’ demographic and disease-related data. A total of 128 patients (rheumatoid arthritis, n = 44; ankylosing spondylitis, n = 45; psoriatic arthritis, n = 23; and adults with juvenile idiopathic arthritis, n = 16) participated in this study. Among the entire patient population, SUA levels significantly increased 3 months after starting treatment with TNFis (279.5 [84.0] vs. 299.0 [102.0] μmol/l, p < 0.0001), while the levels of CRP, IL-6, IL-8, and MCP-1 significantly decreased. Male sex was the most powerful baseline predictor of ΔSUA in univariate and multivariate models. None of the measured laboratory-based parameters had statistically significant effects on the magnitude of ΔSUA. 3 months of anti-TNF therapy increased the levels of SUA in patients with SARDs, but neither the measured pro-inflammatory cytokines nor the oxidation to allantoin appeared responsible for this effect.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Cytokines; Inflammation; Oxidative stress; Rheumatic diseases; Uric acid